Auditory processing in children and adolescents in situations of risk and vulnerability - Murphy, Cristina Ferraz Borges; Pontes, Fernanda; Stivanin, Luciene; Picoli, Erica; Schochat, Eliane (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Children and adolescents who live in situations of social vulnerability present a series of health problems. Nonetheless, affirmations that sensory and cognitive abnormalities are present are a matter of controversy. The aim of this study was to investigate aspects to auditory processing, through applying the brainstem auditory evoked potential (BAEP) and behavioral auditory processing tests to children living on the streets, and comparison with a control group. DESIGN AND SETTING: Cross-sectional study in the Laboratory of Auditory Processing, School of Medicine, Universidade de São Paulo. METHODS: The auditory processing tests were applied to a group of 27 individuals, subdivided into 11 children (7 to 10 years old) and 16 adolescents (11 to 16 years old), of both sexes, in situations of social vulnerability, compared with an age-matched control group of 10 children and 11 adolescents without complaints. The BAEP test was also applied to investigate the integrity of the auditory pathway. RESULTS: For both children and adolescents, there were significant differences between the study and control groups in most of the tests applied, with significantly worse performance in the study group, except in the pediatric speech intelligibility test. Only one child had an abnormal result in the BAEP test. CONCLUSIONS: The results showed that the study group (children and adolescents) presented poor performance in the behavioral auditory processing tests, despite their unaltered auditory brainstem pathways, as shown by their normal results in the BAEP test.